2021
DOI: 10.3390/su13041932
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability in Construction Projects: A Systematic Literature Review

Abstract: This paper aims to identify the major research concepts studied in the literature of sustainability in construction projects. Two bibliometric analysis tools—(a) BibExcel and (b) Gephi, were used to analyze the bibliometrics indices of papers and visualize their interrelations as a network, respectively. Therefore, a research focus parallelship network (RFPN) analysis and keyword co-occurrence network (KCON) analysis were performed to uncover the primary research themes. The RFPN analysis clustered the studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 101 publications
(180 reference statements)
0
39
0
1
Order By: Relevance
“…, 2017), in which every keyword p or q is indicated by a node. The weight of an edge between two nodes (keywords) represents the number of papers that have listed both these keywords (Kiani Mavi et al. , 2021).…”
Section: Review Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2017), in which every keyword p or q is indicated by a node. The weight of an edge between two nodes (keywords) represents the number of papers that have listed both these keywords (Kiani Mavi et al. , 2021).…”
Section: Review Methodsmentioning
confidence: 99%
“…Consider network N for the co-occurrence of keywords (Rajagopal et al, 2017), in which every keyword p or q is indicated by a node. The weight of an edge between two nodes (keywords) represents the number of papers that have listed both these keywords (Kiani Mavi et al, 2021). Therefore, the co-occurrence matrix B with arrays b pq is formed using Eq.…”
Section: Search Criteria and Screening Phases For Reviewmentioning
confidence: 99%
“…To find articles focused on policies designed for the motorcycle market, we carried out search of the literature in Scopus database. This is one of the largest databases of peer-reviewed scientific information [53], which is highly valued and widely used in other bibliometric studies [54][55][56][57][58][59][60][61], because it covers a comprehensive range of fields, such as science, technology, medicine, social science, and arts and humanities. Furthermore, several operating functions in Scopus facilitate bibliometric analyses [56].…”
Section: Data Collectionmentioning
confidence: 99%
“…Research on project management and sustainability is growing steadily, and the role of projects in sustainability change is widely recognized (Aarseth et al, 2017; Huemann & Silvius, 2017; Kiani Mavi et al, 2021). The integration of project management and sustainability poses an interesting contradiction, as project management is focussed on precise objectives and time-bound activities, whereas sustainability is concerned with long-term challenges (Sabini et al, 2019).…”
Section: Introductionmentioning
confidence: 99%